Co-Existance of Dengue Fever And Malaria In Patients Presenting With Febrile Ilness - Samsoor Zarak, Muhammad; Khan, Jaffar; Malik, Maham; Ul Haq, Noman; Nasim, Aqeel; Riaz, Sohail; Saood, Muhammad; kakar, Saliha; sana, Hamaiyal; Arshad, Zara; Ullah, Asad (Journal of Medical Biomedical and Applied Sciences, 2018)
Objective: To determine the co-existence of dengue fever and malaria in patients presenting with febrile illness.Introduction: Malaria is worldâs most widespread infection. It occurs throughout most of the tropical regions ofthe world. Plasmodium falciparum predominates in Africa, plasmodium vivax is more common in Central America,plasmodium malariae is found in most endemic areas, especially throughout Africa, plasmodium ovale is unusualoutside of Africa and comprises <1% of isolates. The rationale of this study is to confirm d ual i nfections (malariaand dengue) in our setup in order to treat and prevent complications of co-existing disease. Secondly, both diseasesare associated with bleeding disorder hence by making proper diagnosis we can prevent risk of bleeding.Material And Methods: A cross sectional study was done at Department of Medicine, Shaikh Zayed MedicalComplex, Lahore. The time duration of the study was from 5-10-2016 to 5-4-2017. This study a total of 150patients were observed. By taking all aseptic measures 3ml blood was taken in three bottles (one CBC and twoserum bottles). One serum bottle was clearly marked with hospital number and patient name and sent to theoutside laboratory in order to check Anti Brucella antibodies, typhidot test and Paul Bunnel and Monospot test ofInfectious mononucleosis. 2nd serum bottle was clearly marked with hospital number and patient name and sent tothe laboratory in order to check dengue virus antigen, dengue serology, CBC bottle was sent to check malariaparasite by making thick and thin films. Results: In the present study mean age of study patients was 40.02 +14.4 years. The female and male gender proportions were 61% and 39% respectively. Our study concludes thatthe co-existence of dengue fever and malaria was 19% in patients presenting with febrile illness.Conclusion: Our study concludes that the co-existence of dengue fever and malaria was 19% in patients presentingwith febrile illness.